Voices Of Women As Expressed In Manju Kapur’s Difficult Daughter’s (International Journal of Food and Nutritional Sciences, 2022)
Interpersonal relationships have found a major place in the recent Indian writings. While Patriarchal systems have governed and still governing the society to an extent, the women too have started rising their voices against this oppression. But the sad state witnessed in the society is that, women are forced to follow the customs and beliefs not by the men, but by the women. A perfect woman in the Indian society should be calm, obedient, obeying any orders and if she raises her voice, she is called by many names. Kapur, in her novel brings out the voices of women at different levels in the society and how education helps them to survive the oppression on them.